Introduction to statistical decision theory : utility theory and causal analysis - Bacci, Silvia; Chiandotto, Bruno (Boca Raton, FL : CRC Press, 2020)
Introduction to Statistical Decision Theory: Utility Theory and Causal Analysis provides the theoretical background to approach decision theory from a statistical perspective. It covers both traditional approaches, in terms of value theory and expected utility theory, and recent developments, in terms of causal inference. The book is specifically designed to appeal to students and researchers that intend to acquire a knowledge of statistical science based on decision theory. Features Covers approaches for making decisions under certainty, risk, and uncertainty Illustrates expected utility theory and its extensions Describes approaches to elicit the utility function Reviews classical and Bayesian approaches to statistical inference based on decision theory Discusses the role of causal analysis in statistical decision theory
OCLC-licensed vendor bibliographic record.
Keywords: Statistical decision; Mathematical statistics; Statistics; MATHEMATICS / Probability & Statistics / General